Levetiracetam: Pharmacological properties, safety and efficacy in the pediatric population with epilepsy - Ansari, Zarrin A.H. (Journal of Pediatric Neurology, 2014)
Age-specific distribution of epilepsy is bimodal, with the highest incidence being in childhood. Seizures can affect life as early as day one. There is a paramount variation of epilepsy in childhood and adolesence with regards to its etiology and prognosis. Antiepileptic drugs, being the mainstay of treatment, necessitates that their use in this vulnerable age group must be made after a thorough look into the available evidence. The data on levetiracetam (LEV), a second-generation antiepileptic, spans from randomized controlled trials to case reports in various pediatric epilepsy and epileptic syndromes. This review is a compilation and critical analysis of the data on the differences in the pharmacokinetic properties of LEV in children versus adults, drug-interactions, efficacy of LEV in various contexts, namely, as add-on, as monotherapy, in partial and generalized seizures, in specific epilepsy syndromes such as benign epilepsy with centrotemporal spikes, epileptic syndromes with continuous spike and wave during sleep, Lennox-Gastaut syndrome, Jeavons syndrome and epilepsy associated with tuberous sclerosis. LEV is an effective option for the treatment of partial-onset seizures as both an add-on in refractory epilepsy and monotherapy in newly diagnosed focal epilepsies. There are preliminary but promising data available on various epileptic syndromes and epileptic encephalopathies that can nudge researchers towards further work in these areas in order to generate evidences that is more substantial. The safety and tolerability profile of LEV is favorable, though, behavioral and neuropsychiatric adverse events are reportedly higher in children versus adults. The neuropsychiatric adverse events are often observed against the background of previously existing behavioral issues and neurocognitive impairments.
Keywords: Levetiracetam; pediatrics; safety; efficacy; pharmacokinetics; epilepsy syndromes; myoclonic; absence; refractory epilepsy